Trật tự từ trong tiếng Pháp và tiếng Việt - Phạm, Thị Tình (H. : ĐHQGHN, 2017)
The issue of the order of words has been researched for a long time in the way of logic and rhetotic. The order of words has been also studied a s a specific characteristics of type of language in the way of syntax, semantics and lately in the way of pragmatics. It plays a role in showing the focus emphasized and expressing the modality.